Religious Character Education in Term of Moral Knowing: A Case Study at an Elementary School in Surakarta - Susilowati, Arum; Fauziati, Endang; Rahmawati, Fitri Puji; Rahmawati, Laili Etika (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2023)
The purpose of this study is to find out and analyze: (1) how is the implementation of religious character education in term moral knowing students in classroom learning, (2) how is the implementation of religious character education in term moral knowing students into extracurricular programs, (3) how is the implementation of religious character education in term moral knowing student in self-development programs at an Elementary school in Surakarta. This study used a descriptive qualitative approach. Data collection techniques use interviews, observations, and documentation studies. The primary data sources were obtained from the results of researcher's observations and interviews with school principals, teachers of the Aqidah Akhlak subject, classroom teachers and 31 students in class 4A at an Elementary school in Surakarta. While the secondary data was obtained by researchers from existing sources in the form of evidence, notes and files. Data is analyzed by performing data reduction, data presentation, and data verification. The results of the research show that the implementation of religious character education in term moral knowing students in learning Fiqh, Arabic, Aqidah Akhlak, Al-Qur'an and Hadits, and Kemuhammadiyahan. The implementation of religious character education in term moral knowing students into extracurricular programs is calligraphy, tapak suci, hizbul wathan and tahfidz Qur'an. Implementation of religious character education in term moral knowing student in self-development programs is the habit of praying dhuha, Friday infaq, cultum, tadarus, Friday prayers, dhikr after prayers, memorizing verses of the Al-Qur'an, memorizing short hadits and memorizing daily prayers at an Elementary school in Surakarta.